Faktor-Faktor Yang Berhubungan dengan Terjadinya Noise Induced Hearing Loss (NIHL) Pada Pekerja PT Mekar Armada Jaya - Desi Nafalia; Achmad Husein; Yamtana Yamtana (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
Noise induced hearing loss (NIHL) is one of occupational related diseases which is most found in many industries. NIHL is an impairment of auditory sense as a result of continuous noise expo-sure which has excessive intensity and occured for a long time. Mekar Armada Jaya Company, in its production process, uses machines and equipments that emit loud sound, and therefore it may interfere ear function of the workers. This study was aimed to determine what factors are re-lated with NIHL among the workers, by conducting a cross sectional survey. With using stratified sampling technique, 36 respondents were selected and their hearing capability was measured by using audiometry. Pearson product moment correlation test and chi-square test at 95 % signi-ficance level were used to analyse the data, and the results showed that factors which had relati-onship with NIHL incidence were: noisy time (r = 0.636; p = 0.001), time away from noisy envi-ronments (r = -0.441; p = 0.007), and drug use (p = 0.012).